STRATEGI MARKETING PUBLIC RELATIONS DINAS KOMERSIAL PT. ANGKASA PURA II DALAM MEMPERTAHANKAN LOYALITAS MITRA USAHA DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Utami, Rizky Sri; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
PT. Angkasa Pura II Pekanbaru is an airport company which is force to deliver a good service for all passengers and airport visitors. One of the services that they have to give to the passengers is tenant outlet from business partners at Sultan Syarif Kasim II Airport Pekanbaru. Therefore, as a work unit, Commercial Division who handled all business partners should have special strategy to maintaining business partners’ loyalty. This research aimed to study how Marketing Public Relations’ steps are made and the activities of Marketing PR that commercial division done to maintaining business partner’s loyaltyThis research uses the qualitative research method. The subject of reasearch consisting of one assistant manager and two staff of Commercial Division PT. Angkasa Pura II Pekanbaru, and also five business partners in Sultan Syarif Kasim II Airport which chosen in using a purposive technique. This study uses observation, interview and documentation as the data collection technique. To achieve the validity of the data this research used triangulation and extension of participations.The result of the research is showing that the steps of Marketing PR that made by Commercial Division for maintaining business partner’s loyalty are by analyzing data and facts which become the reasons why business partners are quit, then making a planning the program which involving the business partners in it, one of the planning is by making a segmentation for business room at Sultan Syarif Kasim II Airport. The next step is implementation or action, in taking action they did the marketing PR activities, such as event, publication through social media and others. The last step is an evaluating, to known how far Marketing PR strategy are success, it can be known by looking by the increase of the business partners’ income and also extended the contract. The most frequent of the form of marketing PR strategy are publication through social media and official website, making events at Sultan Syarif Kasim II Airport, speech, and social activities that involve the business partners.Keyword: Strategy, Marketing Public Relations, Loyalty